Symptoms of Depression and Preterm Birth Among Black Women. Issue 5 (September 2018) - Nutor, Jerry John; Slaughter-Acey, Jaime C.; Giurgescu, Carmen; Misra, Dawn P.
Abstract: Objective: To investigate the relationship between depressive symptoms and preterm birth (PTB) while adjusting for social support, both general and from the father of the baby. Design: Retrospective study design. Setting: Participants of the Life-course Influences of Fetal Environments (LIFE) study were recruited from a suburban hospital in Metropolitan Detroit, Michigan. Participants: The LIFE data consisted of 1, 410 self-identified Black women age 18 to 45 years; 1, 207 women were included in this analysis. Methods: Women were interviewed using a structured questionnaire administered 24 to 48 hours after birth during their postpartum hospitalization. Data on the newborns and their mothers' health were collected through medical record abstraction. The Center for Epidemiologic Studies Depression Scale (CES-D) was used to measure symptoms of depression. The CES-D scores ≥23 were considered severe symptoms of depression. Modified Poisson regression models were built using a stepwise approach to assess association between symptoms of depression and PTB. Results: Approximately, 17% of women had a PTB and 20% of women in the sample had a CES-D scores ≥23. Women who had CES-D score ≥23 were about 70% more likely to have a PTB compared with women with CES-D scores <23 (PR = 1.68, 95% CI: 1.24-2.16) after adjustment for both general social support and father of the baby support. Conclusion: Women with CES-D scores ≥23 were almost twice more likely to have PTB compared with women with CES-D scores <23. Referrals for mental healthcare providers might benefit women with symptoms of depression and improve birth outcomes. Nurses should encourage women to seek support beyond the father of the baby. Abstract : This study evaluated the relationship between depressive symptoms and preterm birth among Black women while adjusting for general social support and support from the father of the baby. Approximately 17% of women in the sample had a preterm birth. One-fifth had severe depressive symptoms based on the Centers for Epidemiologic Studies Depression Scale. Women with severe depressive symptoms were almost twice as likely to give birth preterm when compared to women who did not have these symptoms.